Maritime Character Formation Training for the Nahdlatul Ulama Students Association (IPNU) in Gowa Regency: Pelatihan Pembentukan Karakter MARITIM bagi Ikatan Pelajar Nahdlatul Ulama (IPNU) Kabupaten Gowa - Muslimat; St. Nursa’adah; Andi Meirling; AB. Takko Bandung; Muh. Akhdan Abizar Anwar; Indarwati (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2023)
Maritime Character Formation Training for the Nahdlatul Ulama Student Association (IPNU) in Gowa Regency is a community service program aimed at providing understanding and awareness of the importance of understanding, strengthening, maintaining, and applying maritime character for the younger generation in daily life. This training reinforces the idea that every individual in Indonesian society should make maritime character their identity. This community service involves the younger generation of IPNU in Gowa Regency using active and participatory methods. The training teaches the importance of applying maritime character for the younger generation in shaping their future and the future of the nation. Character imbued with humanistic, wise, religious, innovative, resilient, integrity, and independent values is a capital in facing future challenges and helps build the nation to become more advanced, stronger, and highly competitive in the global arena. The formation of maritime character needs to be continuously developed and carried out widely so that the message conveyed can reach the entire community.